Prevalence of low health literacy levels in decompensated heart failure compared with acute myocardial infarction patients. (5th February 2021) - Perrin, Adèle; Abdalla, Gergis; Viprey, Marie; Delahaye, François; Mewton, Nathan; Ovize, Michel; Sebbag, Laurent; Bochaton, Thomas; Dima, Alexandra L.; Bravant, Estelle; Schott, Anne‐Marie; Haesebaert, Julie
Abstract: Aims: Health literacy (HL) is a health determinant in cardiovascular diseases as the active participation of patients is essential for optimizing self‐management of these conditions. We aimed to estimate the prevalence of low HL level in patients hospitalized for acute myocardial infarction (AMI) or acute decompensated heart failure (ADHF) and explore low HL determinants. Methods and results: A prospective cross‐sectional study was performed in three cardiology units. HL level was assessed using Brief Health Literacy Screen (BHLS) and categorized as low or adequate. Dimensions of HL were assessed with the Health Literacy Questionnaire (HLQ). Associations with sociodemographic factors, disease history, and comorbidities were explored. A total of 208 patients were included, mean ± SD age was 68.5 ± 14.9 years, and 65.9% were men. Patients with ADHF were significantly older and more often women than AMI patients. Prevalence of low HL was 36% overall, 51% in ADHF patients, and 21% in AMI patients ( P < 0.001). After adjustment for sociodemographic factors, patients with lower income (€<10 000 per year, adjusted odds ratio = 10.46 95% confidence interval [2.38; 54.51], P = 0.003) and native language other than French (adjusted odds ratio = 14.36 95% confidence interval [3.76; 66.9], P < 0.002) were more likely to have low HL. ADHF patients presented significantly lower HLQ scores than AMI patients in five out of the nine HLQ dimensions reflecting challenges in access to healthcare. Conclusions: Prevalence of low HL was higher among ADHF patients than among AMI patients. Low HL ADHF patients needed more support when accessing healthcare services, and these would require more adaptation to respond to low HL patients' needs.